Unlocking Adolescent Mental Health: Exploring Social Determinants and Depression With the Social Ecological Model - Lauren B. Robins; Danielle Rodgers; Yusuf Barburoglu; Jasmine Griffith; Cearra L. Arnold (Journal of Human Services)
Employing the robust framework of the Social Ecological Model (SEM) and drawing insights from the Social Determinants of Health (SDOH), this research sought to uncover the interplay between SDOH and mental health among adolescents. With a focus on depression, the study unraveled how various social determinants, both individually and collectively, shape the mental well-being of adolescents, leveraging the rich dataset provided by the National Survey of Children’s Health 2018. Utilizing advanced statistical techniques, the study revealed the predictive power of SDOH in understanding adolescent mental health. Results illuminate the significant influence of social determinants on depression, underscoring the imperative for a comprehensive approach to mental health interventions. Notably, the findings highlight how the absence of adverse determinants mitigates the risk of negative mental health outcomes among adolescents, while also shedding light on the correlation between adverse determinants and depression. These findings underscore the critical role of interdisciplinary collaboration among healthcare professionals in minimizing the detrimental impact of adverse determinants on adolescent mental health. By recognizing and addressing the multifaceted influences of social determinants, stakeholders can work together to foster environments conducive to positive mental well-being among adolescents.